Renaissance Sdn. Bhd. lucy glucose drink / Muhammad Zairi Ab. Rahim …[et al.] - Ab. Rahim, Muhammad Zairi; Mohd Azhar, Muhammad Azlan; Wan Sulaiman, Wan Mohammad Fahim Najmi; Abdullah, Anis Muzakkir; Mohd Ghazali, Ahmad Safi (2016)
We are from Renaissance Sdn. Bhd. proudly presents our newest product from our company which is LUCY. It is a supplement drink that were made out of pure glucose. What makes our product differs from others is that our raw materials comes from the durian and pineapple peels which basically is just a waste product from the fruit. Our target customers focuses mostly on daily consumers who usually doing vigorously activities and heavy workers. This drink will provide them enough energy for all day long and also control their sugar intake for the diabetics which makes them healthier and energize. Some of the existing energy or supplement drinks in the market right now does not highlight where do they get the raw materials from and mostly the raw materials such as sugar were come from their main source such as sugar cane. However, with our technology we can get sugar from an alternate source and maximize its usage and also minimize the waste product as possibly as we can. We are fully confident that our product can generate enough profit to our company and make our business feasible. This is due to introduction of our new intakes on supplement and energy drinks and make it to whole new level. Also, we were determined that our product will give a whole new idea on how waste products can be manipulated to be as a good resources and thus bring a whole new green technology to this industry.